2021
DOI: 10.1101/2021.11.08.467799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Inhibition Prevents Caveolin-1-dependent Calcifying Extracellular Vesicle Biogenesis

Abstract: BackgroundChronic kidney disease (CKD) increases the risk of cardiovascular disease, including vascular calcification, leading to higher mortality. Release of calcifying extracellular vesicles (EVs) by vascular smooth muscle cells (VSMCs) promotes the ectopic mineralization of vessel walls. Caveolin-1 (CAV1) protein plays a key role in formation of calcifying EVs in VSMCs. Epidermal growth factor receptor (EGFR) co-localizes with and influences the intracellular trafficking of CAV1.MethodsWe computationally an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The evidence of EGFR involvement in the development of VC arises from the study of Nik et al (27), as illustrated in Figure 3. In a genetic association study, EGFR mutation has been strongly associated with the incidence of VC.…”
Section: Role Of Receptor Tyrosine Kinase In Cardiovascular Calcifica...mentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence of EGFR involvement in the development of VC arises from the study of Nik et al (27), as illustrated in Figure 3. In a genetic association study, EGFR mutation has been strongly associated with the incidence of VC.…”
Section: Role Of Receptor Tyrosine Kinase In Cardiovascular Calcifica...mentioning
confidence: 99%
“…Another study assessed the relationship of CAC with CVD and cancer mortality and found a relationship between CAC with CVD and cancer mortality, which significantly differed for women and men (111). Additionally, a molecular study has shown an increase in CAV-1 in calcifying VSMC (27), which is similar to malignancy (112).…”
Section: Evidence Linking Cancer Tyrosine Kinase Inhibitors and Cardi...mentioning
confidence: 99%
See 1 more Smart Citation